Polio Vaccine Struggles: FAIR and the Failed Reintroduction of Inactivated Polio Vaccine, 1975–1985. (14th October 2021) - Baylac-Paouly, Baptiste; Hendriks, Jan; Blume, Stuart
Summary: This article discusses the strategies and trajectories deployed by the Forum for the Advancement of Immunization Research (FAIR) to rehabilitate Salk's inactivated polio vaccine (IPV), at a time when Sabin's oral polio vaccine (OPV) had come to dominate the global polio vaccine market. FAIR was an international coalition of scientists and institutions that undertook specific field studies to establish the conditions under which IPV could usefully be introduced in developing countries. Regardless of the evidence it gathered, FAIR failed to convince WHO to integrate IPV into the Expanded Programme on Immunization (EPI). This study of the life of IPV vaccine beyond its initial development and introduction, provides insights in the interplay of evidence and interests in the political decisions made around vaccination.